Pengaruh Non-Performing Loan (NPL), Equity to Total Assets (EQTA), Operating Expense (OE) terhadap Net Interest Margin (NIM) Bank di Indonesia Periode 2017-2021 - Kumba Digdowiseso; Farraz Azzahra Alfirah (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to determine the effect of the variables measured, namely non-performing loans (npl), equity to total assets (eqta), operating expense (oe) on the net interest margin (nim) of banks in Indonesia for the 2017-2021 period. The population in this study are 20 companies in the banking sub-sector that are still listed on the Indonesia Stock Exchange for the 2017-2021 period. The sampling technique is by purposive sampling method and obtained as many as 10 companies. The research data were analyzed using the panel data regression method with a significance level of 0.05 using the STATA 16 program. The results of this study indicate that the variables indicate that the variable Non-Performing Loans has a negative and insignificant effect on the Net Interest Margin. The Operating Expense variable has a negative and insignificant effect on the Net Interest Margin.. Keywords: Net Interest Margin (Nim), Non-Performing Loan (Npl), Equity To Total Assets (Eqta), Operating Expense (Oe).